(untitled) (Research, Society and Development, 2025)
The growing demand for beef driven by population growth requires Brazilian livestock farming to strike a balance between productive efficiency and socio-environmental responsibility. In this context, this study aims to highlight the importance of animal welfare in the pre-slaughter handling of cattle and its relationship with the final quality of the meat. The methodology used was a literature review based on scientific articles and academic publications from the main databases. The results indicate that inadequate practices in the transportation, loading, unloading and stunning of animals increase stress, compromising animal welfare and resulting in economic losses and inferior meat quality, as in the case of DFD meat. On the other hand, the adoption of good practices reduces bruising, improves parameters such as pH and meat tenderness, in addition to meeting legal, ethical and market requirements. It is concluded that investment in technologies and training is essential to promote more humane and sustainable management, which values animal welfare at all stages of the production process.